A Clinicopathological Study of Immunobullous Diseases - Prakash, Annu Elizabeth; Mathai, Jessy Mangalathu; Thankappan, Thundi Parampil; Sulochana, Gopalan (Annals of Pathology and Laboratory Medicine, 2019)
BACKGROUND Vesiculobullous disorders are a group of disorders involving the formation of a fluid filled cavity within or beneath the epidermis, due to the presence of autoantibodies against adhesion molecules in epidermis and dermis. The clinical presentation and the microscopic features of different diseases belonging to this group vary greatly. This study was undertaken to describe the clinical features and the histopathological patterns of immunobullous diseases. METHOD 30 cases of immunobullous disorders who attended Dermatology Outpatient Department were included in the study. Relevant clinical details of these cases were collected and punch biopsies were taken from the site of lesion which were used for routine histopathology. RESULTS Among the 30 cases included in our study, males were found to be more commonly affected than females. The most common immunobullous lesions encountered were Pemphigus Vulgaris(13/30) and Bullous Pemphigoid (10/30). In pemphigus group of diseases, patients presented with small cutaneous and oral vesicles. Pemphigus foliaceous patients showed cutaneous lesions only. Intraepidermal vesicles containing acantholytic cells and inflammatory cells were characteristic histological features of the Pemphigus group. Bullous pemphigoid lesions were large bullae on the limbs and within the oral cavity. Most of the cases of Bullous Pemphigoid showed the formation of subepidermal bullae predominantly containing eosinophils. CONCLUSION Both the clinical findings and the histological features are invaluable in arriving at a definite diagnosis in immunobullous diseases.